Total scattering cross sections for ethylene by electron impact for incident electron energies from 1 to 2000 eV. Issue 4 (7th October 2013) - Naghma, Rahla; Antony, Bobby
<x xml:space="preserve">Abstract</x> We report total scattering cross sections for C2H4 molecule by electron impact. Calculations are performed by using two different quantum mechanical methods and they cover the energy range from 1 to 2000 eV. For low energy calculations up to 15 eV, UK molecular R‐matrix code through QUANTEMOL‐N software is used, while intermediate to high energy (15–2000 eV) calculations were carried out by applying spherical complex optical potential formalism. Comparison is made with earlier measurements and theoretical data wherever available. A shape resonance is detected around 2 eV due to the 2B2g symmetry of an electronic state that corresponds to the temporary negative ion formation of ethylene. The differential cross sections are also calculated for the energy range from 1 to15 eV for the scattering angles between 0º and 180º. © 2013 Wiley Periodicals, Inc.